RELIGIUSITAS DALAM PENDIDIKAN KIMIA (ESENSI PEMIKIRAN PENDIDIKAN KIMIAWAN KLASIK JABIR BIN HAYYAN) - Edy Chandra (Scientiae Educatia: Jurnal Pendidikan Sains, 2012)
Religiousity has not received adequate attention among scientists and educational researchers. Fundamental problems faced by the Islamic university and school is how to strengthen the integration of religiousity into science education. It should be further explored the life and work of Muslim chemists. In this case, Jabir ibn Hayyan, seems to be the most authoritative figures Muslim chemists to be explored further. This research is based on factual historical research model. The object of this study is a collection of writings Jabir ibn Hayyan Classical Arabic in Mukhtar Rasa `il vol.1 (scripted by Paul Kraus 1935), using a qualitative approach to descriptive analytical method, combining historical and philosophical approach, taking into account the substantial and functional relationship between information and obtained and the views contained in the manuscript.  Jabir had engage religiousity his Philosophical thought on divinity, universe, human, society, and knowledge. He had also enhanced religiousity into educational practice, especially in chemistry education. His thoughts could be simplified as an integrative educational thought and balance. Jabir promote holistic education that integrates the various aspects in a balanced education fields, and encourage positive interaction between educators and learners, prioritize based on experiment and observation.Keywords:  religiousity, chemistry, science, education, philosophy